2019
DOI: 10.1093/mnras/stz2474
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of stars and gas in the star formation deserts of barred galaxies

Abstract: Bars strongly influence the distribution of gas and stars within the central regions of their host galaxies. This is particularly pronounced in the star formation desert (SFD) which is defined as two symmetrical regions either side of the bar that show a deficit in young stars. Previous studies proposed that, if star formation is truncated because of the influence of the bar, then the age distribution of stars within the SFD could be used to determine the epoch of bar formation. To test this, we study the prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…In real galaxies these regions are often found to have "star formation deserts" (SFDs) (James & Percival 2016 with ages older than the average. Stellar populations in the SFDs are slowly refilled by stars trapped by the bar at a later stage (Donohoe-Keyes et al 2019). Since our N -body model lacks significant late time bar growth, the presence of these hollows in our model is perhaps not surprising.…”
Section: Metallicity Assignment From the Actionsmentioning
confidence: 82%
“…In real galaxies these regions are often found to have "star formation deserts" (SFDs) (James & Percival 2016 with ages older than the average. Stellar populations in the SFDs are slowly refilled by stars trapped by the bar at a later stage (Donohoe-Keyes et al 2019). Since our N -body model lacks significant late time bar growth, the presence of these hollows in our model is perhaps not surprising.…”
Section: Metallicity Assignment From the Actionsmentioning
confidence: 82%
“…With the aid of stacking techniques applied to far-UV images, showed that massive barred galaxies (total stellar masses M * 10 10 M ) are typically characterised by a dip in the radial distribution of SF that is not seen in nonbarred systems (see also James et al 2009). These 'SF deserts' indeed exist in barred galaxies (James & Percival 2016Spinoso et al 2017;Donohoe-Keyes et al 2019).…”
Section: Introductionmentioning
confidence: 94%
“…In the absence of an inner ring this region (CR -bar) will correspond to the so-called star formation desert (see e.g. James et al 2009;Donohoe-Keyes et al 2019), while in the presence of an inner ring this region will correspond to star formation inside the ring.…”
Section: Effect Of the Bar On The Inner Disc: Formation Of Inner Ringsmentioning
confidence: 99%